2016
DOI: 10.1097/scs.0000000000002564
|View full text |Cite
|
Sign up to set email alerts
|

Medication-Related Osteonecrosis of the Jaw Around Dental Implants

Abstract: Data confirms that not only surgical insertion of dental implants is a potential risk factor for the development of osteonecrosis but also the presence itself of the implant into the bone can be associated with this disease. Therefore, it is necessary to inform of the increased risk for MRONJ also the patients who have already osteointegrated implants and are going to start the BPT.The risk is lower for patients receiving oral BPs but it exists and seems to be higher if the implant is located in the posterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 21 publications
1
37
0
3
Order By: Relevance
“…Thus, surgical intervention per se should not be overemphasized as the main risk factor for MRONJ development. Similarly, it has been suggested that infection around the implants (peri-implantitis) represents a notable risk factor for MRONJ development (Giovannacci et al, 2016;Troeltzsch et al, 2016). This is also in line with the high success rate after surgery on the jawbone to cure MRONJ lesions (see later).…”
Section: Controver S Ie S On Ris K Fac Tor Smentioning
confidence: 54%
“…Thus, surgical intervention per se should not be overemphasized as the main risk factor for MRONJ development. Similarly, it has been suggested that infection around the implants (peri-implantitis) represents a notable risk factor for MRONJ development (Giovannacci et al, 2016;Troeltzsch et al, 2016). This is also in line with the high success rate after surgery on the jawbone to cure MRONJ lesions (see later).…”
Section: Controver S Ie S On Ris K Fac Tor Smentioning
confidence: 54%
“…tailed single-patient data on ARD type and indication for intake, as well as the duration of intake until MRONJ, were possible to extract from four studies (68 patients)(Giovannacci et al, 2016;Holzinger et al, 2014;Jacobsen et al, 2013;Kwon et al, 2014;Lazarovici et al, 2010;Pogrel & Ruggiero, 2017;Troeltzsch et al, 2016).…”
mentioning
confidence: 99%
“…До настоящего времени почти все сообщения об остеонекрозе на фоне терапии бисфосфонатами касались челюстей и были связаны с такими факторами риска, как тип препарата, способ его введения и длительность курса [2,3,4]. При всей актуальности этой проблемы механизм развития осложнений терапии БФ еще недостаточно изучен, но есть основания предполагать, что ключевыми условиями для развития остеонекроза являются травма кости (например, удаление зубов, оперативное вмешательство на пародонте или имплантация), присоединение инфекционного процесса, воспалительные заболевания в полости рта [5,6,7].…”
Section: патоморфологическая характеристика состояния тканей пародонтunclassified